2011
DOI: 10.1016/j.intimp.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Artin M from extract of Artocarpus integrifolia seeds by Th1 and Th17 immune response on the course of infection by Candida albicans

Abstract: The immunoregulatory effect of Artin M and jacalin from extract of Artocarpus integrifolia seeds (jack extract) against infection with Candida albicans was investigated. Swiss mice received jack extract containing 500 μg protein/ml PBS intraperitoneally (i.p.) or PBS alone and after 72 h were infected i.p. with C. albicans CR15 (10(7)) and sacrificed after 30 min, 2, 6, 24, and 72 h. ELISA analysis revealed that in jack extract-treated mice IFN-γ was predominantly produced versus IL-10 in control mice. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 34 publications
1
22
1
10
Order By: Relevance
“…The administration of ArtinM to mice consistently conferred protection against infections by intracellular pathogens. The Th1-skewed response induced by ArtinM is balanced by the induction of IL-10 production, which prevents exacerbated inflammation [12][13][14][15]. As showed in the present study, the IL-10 inducing property was also demonstrated by y-ArtinM.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The administration of ArtinM to mice consistently conferred protection against infections by intracellular pathogens. The Th1-skewed response induced by ArtinM is balanced by the induction of IL-10 production, which prevents exacerbated inflammation [12][13][14][15]. As showed in the present study, the IL-10 inducing property was also demonstrated by y-ArtinM.…”
Section: Discussionsupporting
confidence: 81%
“…Systemic administration of ArtinM induces Th1 immunity that confers protection against various intracellular pathogens [10,[12][13][14][15]. Topical administration of ArtinM promotes regeneration of injured corneal epithelium and oral mucosa [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…ArtinM is also associated in the stimulation of IL12 production (14). However, in this study no effect was observed in the IL12 mRNA expression by ArtinM treatment.…”
Section: Graphic Representations Of the Effects Of Artinm On P53 (A)contrasting
confidence: 72%
“…ArtinM is a d-mannose-binding lectin found in the seeds of Artocarpus heterophyllus that interacts with N-glycans and is associated with receptors on the surface of phagocytic cells to induce production of inflammatory mediators, such as tumor necrosis factor alpha (TNFα) (13), interleukin 12 (IL12) and interferon gamma (IFNγ) (14). Moreover, the protective effect of ArtinM against intracellular pathogens (15,16,17) and against the development of hematopoietic cancer (18) is well-known.…”
mentioning
confidence: 99%
“…In a previous work, our group verified differential properties of Artin M and jacalin present in an extract of A. integrifolia; jacalin treatment was unable to induce protective immune response and few mice survived a lethal inoculum of C. albicans, whereas Artin M was able to induce Th1 and Th17 protective immune responses, by itself or associated with jacalin [18]. Our group has demonstrated high levels of IFN-γ and IL-17 6 h postinfection in these mice and that Artin M but not jacalin induced TNF-α and IL-12 production by macrophages in vitro.…”
Section: Discussionmentioning
confidence: 70%